Guest Satisfaction and Revisit Intention of Muslim Friendly Hotels in Malaysia - Aini Ma’asor @ Mansor, Myzatul; Puad Mat Som, Ahmad; Amin, Aziz; Ibrahim, Yahaya; Abu Bakar, Norsuhaily; Afgani @ Eusoff, Yendo (International Journal of Engineering and Technology, 2018)
The hotel industry has remained one of the most competitive industries in the 21st century, and there is a great deal of study being done on guest satisfaction and the consequent effects it has on guest loyalty and financial performance. Many studies have demonstrated that hoteliers that have more satisfied guests experience higher guest loyalty and perform better financially compared to their competitors, ensuring continuity of their business in the long term. The overwhelming demand for quality products and services among Muslim travelers in recent years has led to the establishment of Muslim Friendly Hotels (MFH) in Malaysia and other Muslim countries. It is widely believed that Muslims perceive Islam as something more than just a religion - it is a way of life. Hence, the religion shapes their consumption behavior even during travel. Currently, very little research has examined the influence of satisfaction on revisit intention among guests staying at MFH, specifically in Malaysia. Preliminary findings from a survey of hotel guests indicate that there is a significant relationship between guest satisfaction and revisit intention, which further explains the importance of desirable hotel attributes in influencing hotel selection and a guestâ€™s experience.Â Â